Immediate preoperative outcomes of pain neuroscience education for patients undergoing total knee arthroplasty: A case series. (3rd June 2019) - Louw, Adriaan; Zimney, Kory; Reed, Jordan; Landers, Merrill; Puentedura, Emilio J.
ABSTRACT: Background : Standard preoperative education for total knee arthroplasty (TKA) has been shown to have no effect on postoperative outcomes. This may be because such education programs fail to educate patients about pain. Pain neuroscience education (PNE) focuses on teaching people more about pain from a neurobiological and neurophysiological perspective. Design and setting : Case Series. Aim : To determine the immediate effects, if any, of providing PNE before TKA surgery on patient self-report measures. Participants : Twelve patients (female = 10) prior to TKA for knee osteoarthritis (OA). Intervention : Preoperative educational session by a physical therapist on the neuroscience of pain, accompanied by an evidence-based booklet. Main outcome measures : Comparison of pre- and post-PNE self-report measures on knee pain (NPRS), Pain Catastrophization Scale (PCS), fear of movement (TSK), and beliefs about TKA; as well as three physical performance measures – knee flexion active range of motion, 40 m self-paced walk, and pressure pain threshold (PPT). Results : Immediately following the PNE, patients had statistically significant lower TSK scores, increased PPT, and improved beliefs about their upcoming surgery. There were no significant changes in knee pain, function, or flexion active range of motion. Conclusions : Results appear to suggest that immediately after PNE, patients scheduled for TKA had statistically significant changes in fear of movement, decreased sensitivity to pain and positive shifts in their beliefs about their future knee surgery. Larger trials with control/comparison groups are warranted to determine the true effects of preoperative PNE for patients about to undergo TKA.